Variabilidade genética em progênies de polinização aberta de Jatropha curcas - Fernandes, Kairo Henrique Pereira [UNESP]; De Moraes, Cristiano Bueno; Carignato, André [UNESP]; Saturino, Heloisa Mattana; Mori, Neide Tomita [UNESP]; Gouvêa, Cantídio Fernando; Zimback, Léo [UNESP]; De Moraes, Mário Luiz Teixeira; Mori, Edson Seizo [UNESP] (My University, 2015)
The objective of the present work was to estimate the genetic parameters of morphological traits, such as plant growth, fruit and seed production; and oil content and also to provide a source of superior genetic material for the breeding program of Jatropha curcas. For that, a J. curcas open pollination progeny test was set up in São Manuel Experimental Station, of College of Agricultural Sciences (FCA) of São Paulo State University (UNESP). The experimental design was of completely randomized blocks with 30 progenies, three replications, and eight plants per linear plot. We evaluated plants height (ALT), number of branches per plant (NRP), number of inflorescences per plant (NINF), number of fruits per plant (NF), weight of fruits (PF), weight of seeds (PS) and oil content % (TO). The software SELEGEN was the used to estimate the genetic parameters. The individual genetic variation coefficients (CVgi) and progeny genetic variation coefficients (CVgp) at 24 months were 26.7% and 13.4% for height and 21.2% and 10.6% for number of branches. At 48 months the heritability coefficients among the progeny averages (h2mp) were 0.41 (ALT); 0.31 (NRP); 0.77 (NINF), and 0.44 (NF). The coefficient of heritability for individual plant level of oil content (TO %) was very low (h2a = 0.03), therefore, for the heritability of progeny means was higher than the individual level (h2mp = 0.37). Among progenies, some of them were superior for both, and seed production and oil content. We conclude that the present J. curcas population has enough genetic variability allowing obtaining gains through advanced generations.
Genetic variability in open pollinated progenies of Jatropha curcas
Keywords: Genetic parameters; Jatropha curcas; Progenies trail